Lifestyles of students of the Nursing School of the National University of Tucumán, Argentina - Analía Ortigoza; Carlos Jesús Canova Barrios (Revista Finlay)
Background: the healthy lifestyle is established as a shielding factor against the development of diverse chronic illnesses, and in the case of the infirmary student, its adoption impacts in the effectiveness of its future professional practice as educator in health, also about the quality of the borrowed attention. Objective: to describe the behaviors associated to the lifestyles of the students of the University School of Infirmary of the National University of Tucumán in Argentina. Methods: a descriptive, traverse and quantitative study was carried out. 406 students were interviewed with the questionnaire Health Promoting Life Profile II under the Nola Pender pattern. The instrument obtained an alpha of Cronbach of 0,93 (high reliability) in the studied population. Results: the typical age was of 28,63 years. The feminine sex, single and students of the first year. Spiritual growth and manage of the stress were the dimensions with the adult and smaller punctuation, respectively. The average of the lifestyle was of 117,17 (OF: 20,10; IC 95 %: 115,21-119,14) with a characterization of regulating. Conclusion: 3,94 % of those interviewed obtained a lifestyle evaluated as healthy, and the variables that impacted were the age, the sex, the civil state and the year of the plan of studies in which they are inscribed. Its required of the design and implementation of actions them to favor the adoption of healthy lifestyles in the infirmary students to diminish the risk of suffering chronic not transmissible illnesses and contributes to his education on health education.